18FDG PET/CT Tumoral and Neurologic Therapeutic Response in a Case of Anti-GABABR Paraneoplastic Limbic Encephalitis. (20th March 2023) - Ouvrard, Eric; Voulleminot, Paul; Mennecier, Bertrand; Bund, Caroline; Namer, Izzie Jacques
Abstract: A 70-year-old man with a history of small cell lung carcinoma 2 years earlier was addressed for the suspicion of a paraneoplastic limbic encephalitis. Brain 18 FDG PET/CT revealed a bilateral amygdalian and hippocampal hypermetabolism, confirming a limbic encephalitis, and concurrent whole-body 18 FDG PET/CT showed a small cell lung carcinoma plurifocal metastatic recurrence, consistent with a paraneoplastic limbic encephalitis. 18 FDG PET/CT follow-up under chemotherapy revealed an almost complete normalization of brain metabolism and a partial metabolic response of the metastatic recurrence, consistent with the good clinical neurological evolution of the patient. This case highlights the clinical-metabolic imaging correlation in paraneoplastic limbic encephalitis.